The effect of animated folk-tale video on the students’ ability in writing narrative text - Andjar Wulandari (Penerbit STKIP PGRI Bangkalan, 2021)
Writing is one of the English skills that is considered difficult for senior high school students, especially SMAN 1 Bangkalan. The researcher tried to find out the significant increase between folklore animation videos and the conventional method from pre-test to post-test using independent t-test. In this quasi-experimental research, the researcher tried to find out how far the effect of animated folklore videos on the ability to write narrative texts of class XI students of SMAN 1 Bangkalan. In conducting the research, the writer used a quasi-experimental study by collecting data through pre-test, double treatment, and post-test. The research topic consisted of 148 students for the population and was divided into XI E (16 males and 13 females) and XI B (16 males and 14 females). The data were statistically calculated using an independent t-test to find differences in performance between students taught using animated folklore videos and students taught using conventional methods. Then it was found that the significance level was 0.01 or 1% and the observed t value was higher than the critical t value (3.1 > 2.756), which means H_1 is accepted and H_0 is rejected. In conclusion, the use of Animated Folklore Video in teaching narrative writing is appropriate, and the researcher suggests that this media be applied in real-world classroom teaching.